2004
DOI: 10.1002/mame.200300188
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Chitosan‐Gellan Hybrid Capsules Formed by Self‐Assembly at an Aqueous Solution Interface

Abstract: Summary: True spherical capsules are formed by electrostatic polysaccharide interaction between chitosan and gellan gum via polyion complex (PIC) formation in aqueous solutions. Dropwise addition of a chitosan solution into the gellan solution gave spherical capsules whose outside surface was gellan and whose inside was chitosan (chitosanin‐gellanout capsule). Conversely, the addition of gellan into chitosan yields chitosanout‐gellanin capsules. SEM observation revealed a fibrous network spreading along the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 30 publications
5
40
0
2
Order By: Relevance
“…Analyzing the data displayed in Fig. 8, almost complete MKP release occurs in approximately 8 h, which is a longer time compared with the 2 h release of D,L-a-phenethylamine and sodium benzoate by chitosan out -gellan in and gellan out -chitosan in capsules (Ohkawa et al 2004). After 24 h, only small differences in the MKP released quantities are observed between the studied samples, and the released values remain practically the same as after 8 h. Thereafter, it is also observed that the released quantities of the fertilizer are mainly influenced by the concentration of fertilizer used rather than the HAGG-CH hydrogel composition.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Analyzing the data displayed in Fig. 8, almost complete MKP release occurs in approximately 8 h, which is a longer time compared with the 2 h release of D,L-a-phenethylamine and sodium benzoate by chitosan out -gellan in and gellan out -chitosan in capsules (Ohkawa et al 2004). After 24 h, only small differences in the MKP released quantities are observed between the studied samples, and the released values remain practically the same as after 8 h. Thereafter, it is also observed that the released quantities of the fertilizer are mainly influenced by the concentration of fertilizer used rather than the HAGG-CH hydrogel composition.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, other interpenetrating chains of agar and gellan gum showed heterogeneity in their structure and the scale of the distance between the chains comparable to the size of its pores (Wasikiewicz et al 2006). Polyion complexes of gellan gum and chitosan were obtained by electrostatic interaction in the form of spheres and hemispheres, honeycombs and fibers obtained by dripping or spinning, also containing dyes, drugs or protein added to the solution of gellan gum or chitosan (Amaike et al 1998;Ohkawa et al 2004;Yamamoto and Senoo 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This leads us to suggest, in accordance with most previous works, that at the interface of the two components forms a load-bearing strong skin that prevents diffusion of the polycation deep into the filament, resulting in a core-shell strucutre. 42,48,[57][58][59][60] The majority solid component was interpreted to be TOCN based on the color of the wet filament (see Figure 1c) when using dyed TOCN dispersion (blue) and polycation solution (pink, PDADMAC).…”
Section: Resultsmentioning
confidence: 99%
“…Up to date, a limited number of CH-GG polyelectrolyte complexes have been reported as the focus has been on the development of capsules and fibers [161][162][163][164][165][166][167] . For example, Yamamoto and co-workers studied the characteristic structures of the interface between CH-GG due to charge overcompensation on the formation of fibers and capsule 162 .…”
Section: Types Of Wound Dressings Available On the Marketmentioning
confidence: 99%